On Muslim Sexual and Gender Diversity and Lifeworlds beyond Legal Form - Hamzić, Vanja (2013)
The proposition of this brief intervention is threefold. Firstly, it attempts to underscore the value of historical analyses of Islamic law and the past Muslim polities for our present-day understanding of the various Muslim social and legal discourses on sexual and gender diversity. This is particularly important in the wake, in numerous contemporary Muslim communities, of an essentially neo-Victorian propriety dressed in ostensibly ‘Islamic’ legal and moral principles. Secondly, along with many other researches of Muslim sexual and gender diversity, the author of this paper is deeply conscious of the effects of a particular kind of neoliberal discourse, whose appropriation of certain universalising legal categories of sexual and gendered human subjectivity serves its newly found purpose to re-colonise and adapt to the novel forms of capitalist exploitation various locale-specific sexually diverse and gender-variant Muslim communities. In response to this tendency, this paper suggests that we need to critically interrogate the form of law as such in the neoliberal project, both in its purportedly ‘Islamic’ and ‘secular’ emanations, and try to see beyond its omnipresent veil. Thirdly and lastly, what the paper proposes we might see when the veil of neoliberal legal form is removed, in various contemporary local contexts, is what the author calls 'insurrectionary vernacular knowledge' – that is, locale-specific epistemologies of, for example, Muslim sexually diverse and gender-variant communities in Pakistan about the self, law and religion which may in many ways interact with various broader narratives, including those of their respective nation-state, the nominal Islamic school of law or even the ‘universal’ human rights, but which still crucially retain a host of idiosyncratic, inassimilable traits and qualities. The paper argues that a sustained engagement with this kind of dissentious knowledge, which is consistent with the ‘culture of dissent’ in Islamic law sui generis, can reveal some hitherto unchartered ...